Theoretical conception of climate-smart agriculture - Peron A. Collins-Sowah (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2018)
In this paper, I explored the various components and conceptual underpinnings of climate smart agriculture to develop a conceptual framework to better understand climate smart agriculture. Furthermore, I proposed a new definition of "climate smart agriculture" based on the various components of the concept and the need for trade-offs and synergies. "Climate smart agriculture technologies and management practices" was also defined based on pillar three of climate smart agriculture as a necessary condition. I argue that since the buzzword "climate smart" has strictly a climate focus, the concept of climate smart agriculture resonates more on GHG emission mitigation. I however posit that a more concise definition of the climate smartness of agricultural production systems will require empirical measurement of some aspects of the concept. Since climate smart agriculture is defined along three pillars (productivity increases, building resilience and adapting, and GHG emission reduction), key concepts such as productivity, resilience, vulnerability and carbon sequestration provide indicators for future empirical measurements of the climate smart agriculture concept.
Keywords: 330; Climate; agriculture; policies; institutions; theory; concept